Characteristic of cellular immunity in children with recurrent respiratory diseases, depending on the level of immunoglobulin E production - Т. Ye. Shumna; S. M. Nedelska; S. V. Solovieva; V. I. Masur; O. Ya. Kolesnik (Zaporožskij Medicinskij Žurnal)
Purpose. To analyze the indices of cellular immunity in children with recurrent respiratory diseases, depending on the level of IgE production.